LANDASAN FILOSOFIS TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Nur Faizi; Rahmadin Munauwarah; Nuril Fathina (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
This paper aims to explain the philosophical principles or foundations of curriculum development in Islamic education. This paper uses a qualitative research method that is library research, namely by looking for data from books and scientific articles that are relevant to the topic of discussion. The data management technique uses descriptive analysis which is presented by the author in a systematic and objective manner. Data is obtained through documentation, namely collecting data from various literature related to the topic of discussion. The results of the research show that the Islamic education curriculum aims to form a spiritual life in students. It is very necessary to think and practice Islamic education which bases its philosophical principles on the Al-Qur'an and As-Sunnah. The philosophical mindset plays an essential role in curriculum development. Curriculum development requires philosophy as a reference or basis for thinking. In its development, it is always based on philosophical schools which will later color the concept and implementation of the developed curriculum, including: parennialism, essentialism, progressivism, and reconstructionism. The implication of this research is to provide a challenge for Islamic educators, namely to articulate a scheme of philosophical thinking that is systematic and provides a life that functions to lay down and guide the principles and practices of developing Islamic education curricula.